Trial of Mobility Management of Railway in a Local City Area: Lessons from a Case Study in the City of Wakayama - ITO, Tadashi (INFRASTRUCTURE PLANNING REVIEW, 2008)
This paper intended to examine Mobility Management (MM) of railway in a local city area by handling a case study in the city of Wakayama. Based on analysis of two railway lines, change of awareness of residents, behavioral change and promoting effect were took into consideration. As a result, though collection rate of questionnaire and awareness of residents were different between two lines, a certain desirable behavioral change was observed. Moreover, as there is promoting effect of MM in a local railway line, it needs support system to implement MM practically.